An optimal "Click" formulation strategy for antibody-drug conjugate synthesis. Issue 24 (15th December 2020) - Vatansever, Erol C.; Kang, Jeffrey; Tuley, Alfred; Ward, E. Sally; Liu, Wenshe Ray
Graphical abstract: Abstract: As a versatile reaction for bioconjugation, Cu(I)-catalyzed alkyne-azide cycloaddition (CuAAC) has enormous potential in the synthesis of antibody-drug conjugates (ADCs). In order to optimize CuAAC-based ADC synthesis, we characterized kinetically different formulation processes by mimicking ADC synthesis using small molecules and subsequently revealed unique kinetic behaviors of different combinations of alkyne and azide conditions. Our results indicate that under ADC synthesis conditions, for an alkyne-containing drug, its concentration has minimal impact on the reaction rate when an antibody has a non-metal-chelating azide but is proportional to concentration when an antibody contains a metal-chelating azide; however, for an alkyne-containing antibody, the ADC synthesis rate is proportional to the concentration of a drug with a non-metal-chelating azide but displays almost no dependence on drug concentration with a metal-chelating azide. Based on our results, we designed and tested an optimal "click" formulation strategy that allowed rapid and cost-effective synthesis of a new ADC.